The Effectiveness of Wenner-Schlumberger and Dipole-dipole Array of 2D Geoelectrical Survey to Detect The Occurring of Groundwater in the Gunung Kidul Karst Aquifer System, Yogyakarta, Indonesia - Doni Prakasa Eka Putra; Oktanius Richard Hermawan (Geological Engineering Department Universitas Gadjah Mada, 2016)
Until today, geoelectrical survey is the most effective method for groundwater exploration. 2D method or known as horizontal profiling is now the most appropriate method in the geoelectrical survey compare to vertical electrical sounding method. The 2D method of Wenner-Schlumberger and Dipole-dipole configuration proved to be very effective to locate conventional aquifer occurrence on volcanic terrain or sedimentary terrain. Karst aquifer system is an unconventional aquifer and acts very differ in contrast with the conventional sedimentary aquifer. Heterogeneity and discontinuity of limestones in karst terrain will reveal a wide variety of resistivities, hence it is difficult to interpret. This research has important objective to define the effectiveness of the Wenner-Schlumberger and Dipole-dipole configuration in the 2D geoelectrical survey to explore groundwater in the karst area. Field observation of geology and 2D geoelectrical survey were conducted in underground river of Kali Suci Area, Gunung Kidul. In Kali Suci where an endokarst cave was occured on the surface, line survey was placed in the top of the cave and across the geometry of the cave. Measured stratigraphy in the wall of the cave found four types of limestone which consist of packstone, wackestone, grainstone and crystalline limestone. The Wenner-Schlumberger and Dipole-dipole method can detect differentiation of limestone types and also the exposed underground river successfully. However, compared to Wenner-Schlumberger array, Dipole-dipole array reveals less vertical accuration.. Therefore, on this research, the best method to detect water saturated zone or gourndwater in the karst system is the Wenner-Schlumberger method.